Storm of shadows - Dodd, Christina (New York : Signet, 2009)
"When the world was young, twins were born. One brought light to a dark world; the other, darkness and danger. They gathered others around them, men and women destined to use their powerful gifts for good or evil. Today, their descendants walk the earth as the Chosen, and the ultimate battle has begun... Brilliant but proper and predictable, Rosamund Hill has lived her life buried in universities and libraries, discounting the legend of the Chosen as a myth. Until Aaron Eagle shows up at her door. Aaron both unsettles and enthralls her. But she can't resist his offers of clandestine visits to private museums, the hunt for a mysterious prophecy, or a makeover that unleashes her untamed soul. With the promise of a love that will defy fate itself, Rosamund is forced to confront the truth about the Chosen...and the dangerous man who sweeps her into a world of dark secrets."--p. [4] of cover.
Keywords: Scholars -- Fiction; Supernatural -- Fiction; Prophecies -- Fiction; Man-woman relationships -- Fiction; Fantasy fiction; Occult fiction; Love stories